1992
DOI: 10.1056/nejm199205073261904
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Desipramine, Amitriptyline, and Fluoxetine on Pain in Diabetic Neuropathy

Abstract: Desipramine relieves pain caused by diabetic neuropathy with efficacy similar to that of amitriptyline, offering an alternative for patients unable to tolerate the latter. Blockade of norepinephrine reuptake is likely to mediate the analgesic effect of these antidepressant drugs in diabetic neuropathy. Fluoxetine, which blocks serotonin uptake, is no more effective than placebo for the relief of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
396
0
10

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,026 publications
(428 citation statements)
references
References 30 publications
13
396
0
10
Order By: Relevance
“…Despite the proven efficacy of FL and other selective serotonin uptake inhibitors in the treatment of mood disturbances, their efficacy as analgesics has not been established. For example, FL was not better than placebo in the treatment of pain associated with diabetic neuropathy, although AM and desipramine were effective as analgesics (28). We found that the improvement in FM pain resulting from treatment with 20 mg of FL was comparable to that with 25 mg of AM.…”
Section: Discussionmentioning
confidence: 61%
“…Despite the proven efficacy of FL and other selective serotonin uptake inhibitors in the treatment of mood disturbances, their efficacy as analgesics has not been established. For example, FL was not better than placebo in the treatment of pain associated with diabetic neuropathy, although AM and desipramine were effective as analgesics (28). We found that the improvement in FM pain resulting from treatment with 20 mg of FL was comparable to that with 25 mg of AM.…”
Section: Discussionmentioning
confidence: 61%
“…Max et al found that, except in depressed patients, fluoxetine produced no more improvement in pain than placebo. 16 However, Sindrup et al found a significant improvement in patients treated with either paroxetine or citalopram versus placebo. [17][18][19] A possible explanation is that serum levels of the treatment drugs were higher in the Sindrup et al studies.…”
Section: Discussionmentioning
confidence: 99%
“…Max et al compared amitriptyline with desipramine, and fluoxetine with placebo in concurrent, randomized, double-blind, crossover studies. 16 Compared with the placebo group, they found significant and equivalent pain relief in the groups treated with amitriptyline and desipramine ( p Ͻ .05), but no significant improvement in the group receiving fluoxetine ( p ϭ .34).…”
Section: Neuropathymentioning
confidence: 94%
“…This hypothesis is supported by the finding that amitriptyline (5-HT and NE reuptake inhibitor) is superior to desipramine (NE reuptake inhibitor), which is superior to fluvoxamine (5-HT reuptake inhibitor) in providing pain relief. 13 In a crossover study comparing 4-week treatment periods, venlafaxine and imipramine were found to be superior to placebo in relieving DPNP. 14 Other drugs reported to manage DPNP are "anticonvulsants," 15,16 selective serotonin reuptake inhibitors, 17 controlled-release oxycodone, 18,19 and the synthetic cannabinoid CT-3.…”
Section: Introduction Dmentioning
confidence: 99%